Answer:
<u>Given function:</u>
- f(x) = (-x + 2)(x + 1)(x +2)
<u>We can rewrite it as:</u>
- f(x) = - (x - 2)(x + 1)(x +2)
<u>Zeros are:</u>
- - (x - 2)(x + 1)(x +2) = 0
- x - 2 = 0 ⇒ x = 2
- x + 1 = 0 ⇒ x = -1
- x + 2 = 0 ⇒ x = -2
As leading coefficient is negative the function is decreasing.
As the function is of degree 3, it is odd.
<u>Considering the above two factors we can define the shape of the graph:</u>
- It is decreasing function with one local minimum and one local maximum.
<em>See the graph and zero's reflected.</em>
Answer:
x=7, because 56 divided by 8 = 7
Step-by-step explanation:
Answer:
Step-by-step explanation:
3.4 times 2 is 6.8
pemdas for the second one. 2 times 6 is 12. 33+10-12, 31
102/22
4.3636
<span><u><em>The correct answer is:</em></u>
B.
<u><em>Explanation:</em></u>
In order to find the appropriate equation for this example, we need to <u>find one that works for the first point (1, 56). </u>
This means when we put 1 in for n in the equation, we need to get 56 as an answer.
If you place 1 in for n in each of the equations, only B gives you 56.
f(n) = 56(0.5)</span>ⁿ⁻¹<span>,
f(n) = 56(0.5)</span>⁰<span>,
f(n) = 56(1),
f(n) = 56. </span>
No it would be 0. 20-2=18-3=15-4=11-5=6-6=0